Recent Advances in Trajectory Planning and Object Recognition for Robot Sensing and Control - Peng, Gang; Fan, Zhun (Sensors (Basel, Switzerland), 2024)
Nowadays, trajectory planning and control technology has been extensively utilized in industry, agriculture, service, construction, infrastructure inspection, military reconnaissance, disaster management, and other areas [...]